Validation, measurement uncertainty estimation and evaluation of UHPLC greenness for simultaneous determination of metoprolol tartrate and hydrochlorothiazide in binary tablet - Claudia Vilela de Oliveira; Adriano Peron; Anas Rashid; Frank Alonso Gavilano Fajardo; Felipe Rebello Lourenço; Marina Franco Maggi Tavares; María Segunda Aurora Prado (Journal of Taibah University for Science)
A novel green ultra high performance liquid chromatography (UHPLC) method was validated and estimated the measurement uncertainty for simultaneous determination of metoprolol tartrate (MET) and hydrochlorothiazide (HCT) in binary tablet. A Zorbax® SB-C18 column with isocratic elution (flow rate 0.9 mL min−1) at 25°C was used. Analytes and HCT degradation product were separated in approximately 1 min using acetonitrile:water:triethylamine (17:83:0.2, v/v) as mobile phase. Analytical curves were linear with (R2 > 0.99 for MET and HCT)  with detection limits of 2.42 and 1.05 µg mL−1 for MET and HCT, respectively.  Precision measurements showed RSD% from 0.39 to 1.2% and method accuracy by recovery tests was 100 ± 2%. Measurement uncertainties using Eurachem procedure were 100.1 ± 2.8% and 100.3 ± 2.4% for MET and HCT, respectively. This UHPLC method was accurate, precise, linear and selective, making it suitable for pharmaceutical quality control. It also proved eco-friendly compared to other reported methods.